Rapid screening of point mutations of the Neisseria gonorrhoeae parC gene associated with resistance to quinolones. - Deguchi, T (1997)
To detect quinolone resistance-associated mutations within the Asp-86, Ser-87, Ser-88, and Glu-91 codons of the Neisseria gonorrhoeae parC gene, we developed a rapid and simple assay based on amplification of the regions of the parC gene containing the mutations sites by PCR and digestion of the PCR products with restriction enzymes. By using the method of primer-specified restriction site modification, artificial SalI, PstI, EcoRI, and HinfI restriction sites were created in the regions containing the Asp-86, Ser-87, Ser-88, and Glu-91 codons, respectively. The mutations generating alterations at Asp-86, Ser-87, Ser-88, and Glu-91 were detected as failures of SalI, PstI, EcoRI, and HinfI to digest the respective PCR products. Fifty-five clinical strains of N. gonorrhoeae were examined for mutations in the parC gene by this assay. Appropriate mutations at either the Asp-86, Ser-87, Ser-88, or Glu-91 codon were detected in each of 11 strains in which a mutation had previously been observed by DNA sequencing. This rapid and simple assay could be a useful device for screening genetic alterations in the parC gene associated with resistance to quinolones in N. gonorrhoeae.